2017
DOI: 10.1080/00207454.2017.1366906
|View full text |Cite
|
Sign up to set email alerts
|

Parkin, PINK1 and DJ1 as possible modulators of mTOR pathway in ganglioglioma

Abstract: It appears that mutations of parkin, PINK1 and DJ1 may result in the development of both neurodegeneration and tumors. Also, these proteins might be used as markers of disease, thus allowing better diagnosis and therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Given the prominent role of chronic iron exposure in AD, and the increased autophagy latency in the development of severe neuron loss caused by iron accumulation, we then investigated the contribution of autophagy to brain damage. m-TOR is an evolutionarily conserved PI3-kinase family member that plays a key role in integrating different biochemical and growth factor signals, and regulates the occurrence of autophagy [39]. We found that HDI treatment did not significantly affect m-TOR expression in WT mice, but significantly increased its expression in AD model mice (Figure 7(A1,B1), p < 0.01), whereas HDI treatment significantly decreased p-m-TOR expression in both groups (Figure 7(A2,B2), p < 0.01).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the prominent role of chronic iron exposure in AD, and the increased autophagy latency in the development of severe neuron loss caused by iron accumulation, we then investigated the contribution of autophagy to brain damage. m-TOR is an evolutionarily conserved PI3-kinase family member that plays a key role in integrating different biochemical and growth factor signals, and regulates the occurrence of autophagy [39]. We found that HDI treatment did not significantly affect m-TOR expression in WT mice, but significantly increased its expression in AD model mice (Figure 7(A1,B1), p < 0.01), whereas HDI treatment significantly decreased p-m-TOR expression in both groups (Figure 7(A2,B2), p < 0.01).…”
Section: Resultsmentioning
confidence: 99%
“…We found that levels of p-m-TOR were dramatically decreased by HDI treatment, whereas the levels of calpain-1, Beclin-1, LC3A/B, and p62 were elevated. m-TOR is a variety of intracellular protein receptor that regulates the occurrence of autophagy [39]. The observed suppressed phosphorylation of m-TOR indicated that autophagy is induced by HDI treatment in the brain of both WT and APP/PS1 mice [72].…”
Section: Discussionmentioning
confidence: 99%
“…The specific regulatory factors of mitochondrial autophagy have not been completely elucidated (5). However, increasing numbers of studies have linked mitochondrial autophagy function to Parkin (6)(7)(8). In patients with Parkin mutations, the activity of the mitochondrial complex has been demonstrated to be reduced in leucocytes; rat Parkin knockout models exhibit reduced mitochondrial proteins and certain mitochondrial deficits, and an increased vulnerability towards autophagy function was observed in a Parkin deletion model (9).…”
Section: Introductionmentioning
confidence: 99%
“…PINK1 negatively regulated the PI3K/Akt/mTOR pathway [50], which might block mTOR-induced PP2A phosphorylation [51] whose suppression of PP2A activity [31]. In addition, PINK1 dysfunction decreased PP2A activity in in vitro of dopaminergic cell culture and the mouse striatum, suggesting that the protective activity of PINK1 could suppress the inactivation of PP2A [52].…”
Section: U N C O R R E C T E D a U T H O R P R O O Fmentioning
confidence: 99%